NORMATIVE FOUNDATIONS AND CURRENT PROJECTS OF INTERNATIONAL SOCIAL WORK - Lytovchenko, Oleksandr (Theoretical and Methodical Problems of Children and Youth Education, 2023)
The materials of the article present the results of the analysis of normative foundations and current projects of international social work, in particular those aimed at international support of Ukraine in the social sphere. It is accentuated that for Ukraine in the conditions of a full-scale war there is a need to urgently solve a number of important social issues, therefore the theory and practice of social work, which responds to those challenges, becomes especially significant. At the same time, successful steps towards Ukraine’s European integration, in particular, in the social sphere – the entry of the Ukrainian Association of Social Workers into the International Federation of Social Workers (IFSW) in December 2022 – increases the relevance of the study of normative foundations and current projects of international social work. The main research methods are defined as: analysis and synthesis of foreign and Ukrainian sources on social work, materials from official sources and web portals of international social work organizations (International Federation of Social Workers (IFSW) and International Association of Schools of Social Work (IASSW), social work organizations in Ukraine; regulatory documents regarding social work, generalization and systematization of data. It is summarized that the normative foundations, key principles and priorities of international social work are based on a number of documents, such as the Global Definition of Social Work, The Global Agenda for Social Work and Social Development: Extending the Influence of Social Work, The Global Agenda: Commitments to Action and others. Among the relevant documents, these should be noted: Climate Justice Program, Peoples Charter for an Eco-social World, which integrated voices from all around the world, emphasizes the importance of democratic participation in bringing about transformative change. It proposes a transition from economies whose success is measured purely by profit to “sustainable welfare societies”. Normative foundations and key principles of international social work are embodied in practical actions and projects. A number of projects are presented on the website of the International Federation of Social Workers (IFSW). Their topics cover a wide range of social work issues: support for Ukrainian social work (Hub of Social Work Ukraine), increasing sensitivity to the voice of citizens in social services throughout Europe, development of ecological wisdom for social workers, realizing the potential of the young generation of social workers for social change and others.